Tuning the magnetic properties of Sn1?x?yCe4+xCe3+yO2nanoparticles: an experimental and theoretical approach - Aragón F.F.H. (2021)
During the last decade, there was a substantial increase in the research on metal-doped oxide semiconductor nanoparticles due to advances in the engineering of nanomaterials and their potential application in spintronics, biomedicine and photocatalysis fields. In this regard, doping a nanomaterial is a powerful tool to tune its physicochemical properties. The aim of this work is to shine a new light on the role of the neighbouring elements on the oxidation state of the Ce-impurity, from both experimental and theoretical points of view. Herein, we present an accurate study of the mechanisms involved in the oxidation states of the Ce-ions during the doping process of SnO2nanoparticles (NPs) prepared by the polymeric precursor method. X-ray diffraction measurements have displayed the tetragonal rutile-type SnO2phase in all samples. However, the Bragg’s peak (111) and (220) located at 2??29° and ?47° evidence the formation of a secondary CeO2phase for samples with Ce content up to 10%. X-ray absorption near-edge structure (XANES) measurements, at Ce L3 edge, were performed on the NPs as a function of Ce content. The results show, on one side, the coexistence of Ce3+and Ce4+states in all samples; and on the other side, a clear reduction in the Ce3+population driven by the increase of Ce content. It is shown that this is induced by the neighboring cation, and confirmed by magnetic measurements. The monotonic damping of the Ce3+/Ce4+ratio experimentally, was connected with theoretical calculationsviadensity functional theory by simulating a variety of point defects composed of Ce impurities and surrounding oxygen vacancies. We found that the number of oxygen vacancies around the Ce-ions is the main ingredient to change the Ce oxidation state, and hence the magnetic properties of Ce-doped SnO2NPs. The presented results pave the way for handling the magnetic properties of oxides through the control of the oxidation state of impurities. © The Royal Society of Chemistry 2021.